Repercussão da seleção realizada logo após a abertura do bulk na produtividade da soja - Mello, Richard Paglia de (2018)
There is a strong competition among soybean breeding companies in Brazil. To win the competition the breeders gets by year hundreds of populations and evaluate some dozens of thousands progenies, which is the procedure adopted by the soybean breeding companies in almost all over the world. The ideal is to perform as early as possible the evaluation of populations and progenies, to concentrate more attention only in the most promising of them. Therefore, the aim of this research was to evaluate whether the early selection for grains yield of soybean segregating populations or progenies is efficient in South Brazil conditions. The trials were conducted in the agricultural years of 2014/15, 2015/16 e 2016/17 in four cities of Parana State. Ten segregating populations were used, being conducted in bulk until the F4 generation. In 2014/15 were evaluated 110 progenies F4:5, from each of the populations. Based on yield grains were selected the twenty best progenies from each of the populations and identified randomly twenty progenies of each population. In the 2015/16 harvest all the progenies, now in F4:5, were evaluated in three places and in the 2016/17 harvest in F4:7, were evaluated in two places, in this two harvests there were three controls cultivars adapted to the region. For analysis the experiments were performed a variance analysis considering the environments/sites as repetitions. The genetic and phenotypic parameters were estimated. In conclusion the progenies selection in F4:5 wasn’t effective, however, the populations selection showed that can be a god strategy for the soybean breeding companies.